Then and Now: Dams (The Biblical archaeology review, 2026)
Today, dams serve a wide range of purposes: diverting rivers and streams, creating reservoirs, generating hydroelectricity, and so on. However, dams are far from a modern invention, with the world’s oldest known dams dating back nearly six millennia. The Great Dam of Marib in western Yemen, which dates to the early first millennium BCE or […]